IMPLEMENTATION OF PUBLIC SERVICES FOR MAKING E-KTP AND FAMILY CARDS IN LAMPUNG PROVINCE FROM AN ISLAMIC PERSPECTIVE - Susanto, Is; Hanif, Hanif; Fuadi, Fatih (Universitas Djuanda, 2024)
This article aims to look at the implementation of public services for making E-KTP and Family Cards in Lampung Province and then look at it from an Islamic perspective. This article uses a qualitative research method with a phenomenological approach as a framework and method of analysis. The data collection stage uses interview, observation, and documentation methods. While the data analysis method uses descriptive analysis method with conclusions drawn through in-depth interview data and theories with an inductive framework. The results of this study indicate that the implementation of Public Services for Making E-KTP and Family Cards in Lampung Province can be seen from five dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. Among the existing dimensions, there are several dimensions that have not been implemented optimally and some others have been implemented well. The service seen from the Islamic aspect has been in accordance with Islamic law by applying the principles of musawah, ukhuwah, muhabbah, and ta'awun in the service.